The Application of Semantic Mapping Techniques on Reading Comprehension for Junior High School Curriculum At SMP 22 Medan - Immanuel Padang; Marice Saragih; Sabar Manik; Kurniawan Sinaga (JURNAL ABDIMAS MADUMA, 2022)
Semantic mapping is an excellent strategy to help students engage in higher-order thinking. In learning reading, it is important for the students to make an effort and show their interest. The aims of this community dedication is to improve the student’s reading comprehension ability through semantic mapping technique. This training very beneficial to the students due to their low competence in the reading comprehension skills. In general, the use of semantic mapping in the classroom can be divided into five phases. These are “introducing the topic, brainstorming, categorization, personalizing the map, post-assesment synthesis : a) Introducing the topic: the teacher studies a unit in the syllabus and determines whether or not semantic mapping can be useful. The teacher announces the topic of the unit by drawing a large oval on the board. He states that some teachers display a picture relating to the topic to stimulate students’ thoughts and to get the brainstorming procedure.b) Brainstorming: the teacher draws a blank map which consists of some blank ovals on the board and provides the students with a reading passage. Furthermore, the teacher asks the students to find some information in the passage that are appropriate to be filled into the blank map.c.)Categorization: the teacher does his best to encourage students to see relationships among their ideas in order to form category cluster.d) Personalizing the map: each student makes a copy of the blank map and complete it by using information found in the passage. E) Post-assignment synthesis: The last part of the class period is used to record students’ suggestions from their personal maps to the board version of the map made by the teacher. The discussion will probably be the centre on the amount of information acquired from the reading. Based on the result of the pre-test and post test that given to the students, it was found that there was improvement of the average value between the pre-test and the post test on 59,52 %, where the average value of the pre-test was 44,40 and the post-test 74,60 so it can be concluded that smantic mind mapping technique training was able to increase reading comprehension of the students of SMP 22 Medan Key Words : Semantics Mapping Technique, Reading Comprehension